Hubungan Antara Dimensi Panjang Induk Dengan Pedet Pada Sapi Bali (CORELATION BETWEEN THE SIZE OF THE BODY PART OF DAM AND CALF IN BALI CATTLE) - Saptayanti, Ni Nyoman Janipa; Suatha, I Ketut; Sampurna, I Putu (Buletin Veteriner Udayana, 2015)
This research aimed to determine the relation between the size of the body part of dam and calf in bali cattle and to get cattle’s size influence calve’s size. Twenty cows and 20 calves each 10male calfes and 10 female new born calfes from Getasan village, District of Petang, BadungRegency. Data of the sizes were analyzed by linear regression. While the sex affect on body sizewas determine by T test. T test results indicated that sex of the calf did not significantly affect therelation between the size of the dams with the calves. But there is a relation between the size of the dams with the calves and there is a comparison the size of each dams with it calves. The mostaccurate relation starting from the size of the ear, neck size, size of head , tail size and size of theear
Keywords: calf; bali cattle; size